Structural modification of octadecanoic acid-3,4-tetrahydrofuran diester and the acaricidal activity and mechanism of its derivatives against Sarcoptesscabiei var. Cuniculi - Li, Lixia; Zhang, Yu; Liu, Tao; Xing, Rui; Peng, Shuwei; Song, Xu; Zou, Yuanfeng; Zhao, Xinghong; Jia, Renyong; Wan, Hongping; Yin, Lizi; Ye, Gang; et al. (Frontiers in Pharmacology, 2022)
Octadecanoic acid-3,4-tetrahydrofuran diester is a compound with acaricidal activity isolated and extracted from neem oil. In this study, a series of derivatives were obtained by structural modification of octadecanoic acid-3,4-tetrahydrofuran diester. The acaricidal activity of these derivatives indicated that introduction of benzyloxy substitution at the 2-position of the furan ring and the formation of a benzoate at the 3,4-position of the furan ring (benzoic acid-2-benzyloxy-3,4-tetrahydrofuran diester) could enhance the acaricidal activity. Its acaricidal mechanism is related to interfering "energy metabolism" in S. scabiei, including processes such as citric acid cycle, oxidative phosphorylation pathway and fatty acid metabolism. Additionally, through the activity detection of the mitochondrial complexes of S. scabiei, it was further verified that the acaricidal mechanism of benzoic acid-2-benzyloxy-3,4-tetrahydrofuran diester was related to the energy metabolism system of S. scabiei.